Vitamin K Antagonists After 6 Months of Low-Molecular-Weight Heparin in Cancer Patients with Venous Thromboembolism - Chai-Adisaksopha C; Iorio A; Crowther MA; de Miguel J; Salgado E; Marija Zdraveska; Fernández-Capitán C; Nieto JA; Barillari G; Bertoletti L; Monreal M; RIETE investigators (Elsevier, 2018)
Background: Low-molecular-weight heparin (LMWH) is the treatment of choice in cancer patients with venous thromboembolism. However, data on continuing LMWH treatment beyond 6 months remain scanty. Methods: We used the RIETE (Registro Informatizado Enfermedad TromboEmbólica) registry to compare the rate of venous thromboembolism recurrences and major bleeding appearing beyond the first 6 months of anticoagulant therapy in cancer patients with venous thromboembolism, according to therapy with LMWH or vitamin K antagonists (VKA). We performed a propensity score-matched cohort study. Results: After propensity matching, 482 cancer patients continued to receive LMWH and 482 switched to VKA. During the course of anticoagulant therapy (mean 275.5 days), 57 patients developed venous thrombosis recurrences (recurrent pulmonary embolism 26, recurrent deep vein thrombosis 29, both 2), 28 had major bleeding, 38 had nonmajor bleeding, and 129 died. No patient died of recurrent venous thrombosis, and 5 patients died of bleeding (2 were on LMWH, 3 on VKA). Patients who continued with LMWH had a similar rate of deep vein thrombosis recurrences (relative risk [RR] 1.41; 95% confidence interval [CI], 0.68-2.93), pulmonary embolism recurrences (RR 0.73; 95% CI, 0.34-1.58), major bleeding (RR 0.96; 95% CI, 0.51-1.79), or nonmajor bleeding (RR 1.15; 95% CI, 0.55-2.40), compared with those who switched to VKA, but a higher mortality rate (RR 1.58; 95% CI, 1.13-2.20). Conclusions: In cancer patients with venous thromboembolism who completed 6 months of LMWH therapy, switching to VKA was associated with a similar risk of venous thrombosis recurrences or bleeding when compared with patients who continued LMWH.
Keywords: anticoagulants; cancer; low-molecular-weight heparin; thromboembolism; warfarin